EKSPLORASI KREATIVITAS SISWA MELALUI PEMBELAJARAN SENI RUPA PADA SISWA KELAS II SDN 1 KALAPANUNGGAL - Nurul Athiah; Melsya Firtikasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the creativity of second-grade students at SDN 1 Kalapanunggal through the implementation of Contextual Teaching and Learning (CTL) in art education. A qualitative case study design was employed for this research. Data were gathered through participatory observation, in-depth interviews with teachers and students, and documentation of students' artwork. The data analysis involved data reduction, data display, and drawing conclusions. The findings indicate that the CTL approach, which connects art materials with students' everyday environments, effectively stimulates imagination, increases active participation, and encourages students to express creative ideas. This study concludes that contextual-based art learning is effective in developing the creative potential of early childhood students in elementary school.